STRES BEBAN KERJA DAN TANGGUNG JAWAB POLISI: TINJAUAN LITERATUR - Divania Fazrina; Didik Irawan, Wustari L. Mangundjaya (Adisam Publisher, 2024)
Background: A police officer is someone with a high responsibility for protecting the safety and security of the community and reducing crime rates. Police work in dealing with crime is very dangerous and full of risks, and often with unpredictable threats. To overcome this, the police set tough targets with high discipline and focus, which requires constant preparedness. Consequently, this condition causes stress at work. Method: This article used a method of a literature review. Researchers searched for articles using the Bold database via Google Scholar. The keywords used are